The Electrochemical Conversion of CO2 into Methanol with KHCO3 Electrolyte Using Membrane Electrode Assembly (MEA) - Dedi Rohendi; Nyimas Febrika Sya’baniah; Edy Herianto Majlan; Nirwan Syarif; Addy Rachmat; Dwi Hawa Yulianti; Icha Amelia; Dimas Ardiyanta; Isya Mahendra; Rr. Whiny Hardiyati Erliana (Science and Technology Indonesia, 2023)
The electrochemical conversion process of CO2 into methanol using Membrane Electrode Assembly (MEA) has been done. The MEA consists of a Pt/C catalyst in the cathode and a Cu2O ZnO/C catalyst in the anode. The electrodes were made using the spraying method and then characterized using Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS) methods to determine the ECSA (Electrochemical Surface Area) and electrical conductivity values. Besides that, also X-Ray Diffraction (XRD) and Scanning Electrode Microscopy – Energy Dispersive X-Ray (SEM-EDX) analysis was to determine the crystal and morphological structure. The voltammogram from CV analysis indicated that the ECSA value on the Pt/C electrode was 7.2 m2/g and the Cu2O-ZnO/C electrodes as 0.69 m2/g. The electrode’s electrical conductivity value with Pt/C catalyst was 1.15 x 10−3 S/cm, and the electrode with Cu2O-ZnO/C catalyst was 0.80 x 10−3 S/cm. The results of the XRD analysis confirmed the presence of Cu2O and ZnO on the Cu2O-ZnO/C electrode and Pt on the Pt/C electrode. Meanwhile, the results of the SEM-EDX analysis showed that the Pt/C catalyst was spread more evenly with a larger percentage than Cu2O and ZnO. The result of the conversion of CO2 to methanol was measured using a methanol analyzer with variations in KHCO3 electrolyte concentration, variation of temperature operation, and variation of time operation. The best methanol concentrations after distillation process were 79.06 w/v %, with 1 M KHCO3, at room temperature and 2 hours operation.